The micro-hybrid method to assess transient stability quantitatively in pooled off-grid microgrids. (May 2020) - Veerashekar, Kishan; Flick, Matthias; Luther, Matthias
Highlights: Successful development and verification of the micro-hybrid method. Detailed analysis of the degree of system stability with respect to clearing times. Clustering microgrids has a negative impact on the transient stability. Solid foundation for the quantitative stability assessment in hybrid microgrids. Abstract: In interconnected off-grid microgrids an in-depth knowledge of dynamic limits can be obtained by performing quantitative transient stability assessment. Quantitative stability results using the new hybrid method can be used for optimal generation dispatching, adjusting protection system settings, optimal clustering of microgrids etc. However, a discrepancy in the profiles of kinetic and potential energy has been noticed. Therefore, in this research work an improved new hybrid method, the so-called micro-hybrid method, was developed by adjusting the transient energy function, which is valid for transmission systems. Further, the new approach was validated and applied in a stand-alone multi-machine microgrid comprising detailed dynamic models of diesel generators with fast-reacting controllers. Finally, the transient stability of three clustered microgrids was assessed quantitatively. From the results it can be concluded that the profiles of the energies obtained by using the micro-hybrid method are exact mirror images. The critical fault clearing times can be corrected based on the profiles of the system stability degree and stability reserve degree of individual generators for different clearing times. Lastly, pooling of the investigated microgrids has a negative impact on the critical clearing times as well as on the profiles of system stability degree with respect to various clearing times.